LEXA MS leg exericse apparatus : an in-bed exercise apparatus that promotes physical exercises with minimal assistance among patients with mild to moderate relapsing-remitting multiple sclerosis to relive spasticity of their lower extremities - Abjelina, Anna Klarissa T.
Relapsing-Remitting Multiple Sclerosis (RRMS) is a type of neurodegenerative diseases which occurs when the immune system malfunctions and attacks the nerve fibers in the central nervous system causing various problems in movements such as: deterioration in motor skills, loss of muscle control, muscle shortening, spasticity especially in the lower extremities. As of date, there is still no cure for multiple sclerosis however; it has been proven that daily exercise through proper physical therapy of the patient's lower extremities play a vital role in slowing the progression of the diseases. Research and interviews were conducted to further understand the current condition of physical therapy as treatment for multiple sclerosis - and from the data gathered, it can be concluded that certain issues put patients in danger of not getting the required daily exercises. Such issues that may hinder patients from getting the required therapy could be their own financial restraints, their families who are too busy in other work, their caretakers with other household chores etc. Because of such circumstances, patients are left with no choice but to exercise on their own. This proves a great challenge to them since moving spastic muscles would require extra effort or force from the patients - which they obviously lack. Due to the degree of difficulty of facilitating exercise on their own and lack of support or assistance while exercising, patients may opt not to exercise at all. Therefore in order to maintain the proper physical therapy for RRMS patients, it is essential to have an easy-to-use exercise apparatus designed specifically for the treatment of their lower extremities. Such device would help promote the maintenance and implementation of the required physical therapy of the patient through independent physical exercise or exercise with minimal assistance.